Optimization of Synthesis of Silver Nanoparticles Conjugated with Lepechinia meyenii (Salvia) Using Plackett-Burman Design and Response Surface Methodology—Preliminary Antibacterial Activity - Laime-Oviedo, Luis Alberto (2022)
“In the present investigation, an ethanolic fraction (EF) of Lepechinia meyenii (salvia) was prepared and fractionated by gradient column chromatography, and the main secondary metabolites present in the EF were identified by HPLC-MS. Silver nanoparticles (AgNPs) were synthesized and conjugated with the EF of Lepechinia meyenii (salvia). The AgNPs synthesis was optimized using Plackett-Burman design and response surface methodology (RSM), considering the following independent variables: stirring speed, synthesis pH, synthesis time, synthesis temperature and EF volume. The AgNPs synthesized under the optimized conditions were characterized by UV visible spectroscopy (UV-VIS), Fourier Transform Infrared Spectroscopy (FT-IR), Dynamic Light Scattering (DLS) and Scanning Transmission Electron Microscopy (STEM). The antibacterial activity of the AgNPs against Staphylococcus aureus (ATCC® 25923) was evaluated. The following flavonoids were identified: rosmarinic acid, diosmin and hesperetin-7-O-rutinoside. The optimized conditions for the synthesis of nanoparticles were pH 9.45, temperature 49.8 ◦C, volume of ethanolic fraction 152.6 µL and a reaction time of 213.2 min. The obtained AgNPs exhibited an average size of 43.71 nm and a resonance plasmon of 410–420 nm. Using FT-IR spectroscopy, the disappearance of the peaks between 626.50 and 1379.54 cm−1 was evident with the AgNPs, which would indicate the participation of these functional groups in the synthesis and protection of the nanoparticles. A hydrodynamic size of 47.6 nm was obtained by DLS, while a size of 40–60 nm was determined by STEM. The synthesized AgNPs conjugated with the EF showed a higher antibacterial activity than the EF alone. These results demonstrate that the AgNPs synthesized under optimized conditions conjugated with the EF of the Lepechinia meyenii (salvia) presented an increased antibacterial activity.“